Surgical Experience and Learning Points in the Management of Foregut Duplication Cysts - Scarpa, Alberto Attilio; Ram, Ashok Daya; Soccorso, Giampiero; Singh, Michael; Parikh, Dakshesh (European Journal of Pediatric Surgery, 2018)
Background Foregut duplication cysts (FDC) have unpredictable natural course and rarely remain asymptomatic. We present our large cohort of FDC to highlight surgical learning points and outcome.Materials and Methods Review of 41 children with FDC (April 1997–April 2015) included demographics, clinical presentation, preoperative investigations, surgical management, post-operative complications, and overall outcome.Results Forty-one children (26 girls/15 boys; male/female [M/F] ratio 1:1.7) had 43 FDC (two cases >1 cyst) consisting of antenatally diagnosed 16 (39%), late with symptoms 21 (51.2%), and incidental 4(9.8%) cases. FDC locations were cervical (3), mediastinal (35), and subdiaphragmatic (5). During all cervical FDC resection, recurrent laryngeal nerve was required to be dissected off the cyst wall. Thoracoscopic resection was feasible in 27 cases, with 4 conversions related to infections and adhesions or accidental injury to trachea/esophagus. Complete resection was achieved in all cases with no recurrence. There was no mortality and morbidity included, chylothorax (1) esophageal injury (1), phrenic nerve injury (1), and tracheal injury (2). The minimally invasive surgery and surgery on asymptomatic lesions significantly affect the outcome by reducing need for chest drain (p = 0.01) and length of hospital stay (p = 0.04).Conclusion This retrospective study confirms the efficacy and safety of thoracoscopic surgery; important learning points were association of common wall with trachea in some superior mediastinal cysts and association of recurrent laryngeal nerve in cervical FDC.
Keywords: foregut duplication cysts; bronchogenic cysts; esophageal duplications; thoracoscopic surgery; children